2018
DOI: 10.15537/smj.2018.10.22679
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological pattern of skin cancer in Western region of Saudi Arabia

Abstract: Objectives:To determine the histopathological pattern of skin cancer in Madinah region of Kingdom of Saudi Arabia (KSA).Methods:This is a retrospective study including all cases with a histological diagnosis of skin cancer diagnosed at the Department of Pathology, King Fahad Hospital, Madinah, Saudi Arabia, between January 2006 and December 2017. Data included age, gender, site and histology of the tumor were collected from histopathological reports and analyzed using Statistical Package for the Social Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 24 publications
(20 reference statements)
2
10
2
1
Order By: Relevance
“…Similar results of less frequency of melanoma were seen in various other studies from Asia. [11][12][13][16][17][18] This is in contrast to the higher frequencies of melanoma from Australia and European countries. 25,-27 In the present study, among the benign tumors, seborrheic keratosis was the most common 19.0%, followed by intradermal nevus 13.3%.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar results of less frequency of melanoma were seen in various other studies from Asia. [11][12][13][16][17][18] This is in contrast to the higher frequencies of melanoma from Australia and European countries. 25,-27 In the present study, among the benign tumors, seborrheic keratosis was the most common 19.0%, followed by intradermal nevus 13.3%.…”
Section: Discussionmentioning
confidence: 70%
“…Similar results of higher frequency of BCC have been reported in studies done in Nepal as well as other countries. 7,[16][17][18][19] But some other studies have shown SCC as the commonest malignant skin tumor. 9-15. Malignant melanoma was found to be the least common malignant tumor constituting only a single case in this study.…”
Section: Discussionmentioning
confidence: 99%
“…is systematic review presented a summary of populationbased data describing the pattern of skin disease in Saudi Arabia. Previous studies investigated the pattern of skin and skin-related diseases in different regions of Saudi Arabia such as Madinah, Al-Khobar, Jeddah, Al-Baha, Hail, Abha, Qassim, and Najran through population-based cross-sectional studies, which reflect the true pattern of skin diseases in Saudi Arabia [6][7][8][9][10][11][12][13][14][15]. Although these included data did not cover every part of Saudi Arabia, the results are generalizable to other populations and reflect the current evidence of the frequency, type, and distribution of skin diseases in different geographical areas in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…e fourteen Saudi studies reported the frequency of the skin disease patterns in different regions in Saudi Arabia with a total sample size of 30436 patients. Only two studies reported the pattern of skin cancers only in southeastern and western regions in Saudi Arabia, with a total sample size of 395 patients with skin cancer [6,10]. Baseline characteristics and summary of the included studies are reported in Table 1.…”
Section: Summary Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation